HUBUNGAN STATUS GIZI DENGAN PERKEMBANGAN PADA BALITA DI DESA BALONGSARI KECAMATAN GEDEG KABUPATEN MOJOKERTO - Eka P, Veryudha; Juli Asri, Dian (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Age 1-5 years is a crucial period in the development of the child. This period was the basis of growth in children, but it also happens the development of language skills, creativity, social awareness, emotional intelligence and running very quickly, which has been the foundation for further development of the child. Nutrition an important part in the growth and development. Growth and development require six major nutrients, namely carbohydrates, proteins, fats, vitamins, minerals and water. Nutrition in it has aligned its relationship to health and intelligence. Nutritional deficiencies during this gold is irreversible (can not be recovered). This study aims to determine the relationship of nutritional status and the development of children under five in rural districts Balongsari gedeg mojokerto district. The design of the study is an analytic correlation with cross sectional approach. Sampling was done by cluster random sampling technique. Number of subjects in this study as many as 129 children. Test analysis using Spearman rho correlation test. the results showed statistical p value 0.005 <a 0.05. The conclusion that can be drawn is that there is a positive and significant correlation with low correlation between nutritional status and development of children under five in the village Balongsari Gedeg District of Mojokerto.Keywords:Nutritional Status,Development,Children under five